Analisis Perubahan Harga Pembinaan Kondominium di Johor Bahru, Johor semasa Perintah Kawalan Pergerakan (PKP) - Ezani, Afif; Rozlin Zainal; Sharifah Meryam Shareh Musa; Noralfishah Sulaiman (Research in Management of Technology and Business, 2025)
The issue of unsold houses in Johor reflects the imbalance between supply and demand in the housing market, which worsened during and after the COVID-19 pandemic due to economic slowdown, reduced purchasing power, and changes in preferences for purchasing condominium homes. Therefore, the objective of this study is to identify the factors influencing price changes and the supply stock of condominium construction units and to measure the strength of the relationship between price change factors and the supply stock of condominium construction units during the Movement Control Order (MCO) period due to the Covid-19 pandemic. The study area was conducted in Johor Bahru, Johor. A quantitative method using 155 survey forms was distributed physically and online, with a response rate of 30.3%. All data was collected and analysed using descriptive statistics such as frequency, mean, and crosstab through SPSS software. The study found that the main factors influencing price changes and supply stock of units are disposable income and macro factors, such as local demand for existing condominium construction in Johor Bahru during the MCO period. Meanwhile, the combination of current housing stock, new construction, vacancy rates, and demand for condominium construction represents the most positive and strong correlation in the condominium construction scenario. In conclusion, this study provides valuable insights to property developers regarding the relationship between price changes, condominium construction stock, and demand during the MCO period, enabling developers to plan more effective development and sales strategies to address the issue of unsold homes while identifying market change patterns and assessing the impact of economic and social policies on demand. This, in turn, allows for data-driven approaches to optimising the condominium supply in Johor Bahru post-MCO.